2019 update of the European AIDS Clinical Society Guidelines for treatment of people living with HIV version 10.0. Issue 10 (3rd September 2020) - Ryom, L; Cotter, A; De Miguel, R; Béguelin, C; Podlekareva, D; Arribas, JR; Marzolini, C; Mallon, PGM; Rauch, A; Kirk, O; Molina, JM; Guaraldi, G; et al.
Abstract : Background: The European AIDS Clinical Society (EACS) Guidelines cover key aspects of HIV management with major updates every two years. Guideline highlights: The 2019 Guidelines were extended with a new section focusing on drug–drug interactions and other prescribing issues in people living with HIV (PLWH). The recommendations for treatment‐naïve PLWH were updated with four preferred regimens favouring unboosted integrase inhibitors. A two‐drug regimen with dolutegravir and lamivudine, and a three‐drug regimen including doravirine were also added to the recommended initial regimens. Lower thresholds for hypertension were expanded to all PLWH and for cardiovascular disease prevention, the 10‐year predicted risk threshold for consideration of antiretroviral therapy (ART) modification was lowered from 20% to 10%. Frailty and obesity were added as new topics. It was specified to use urine albumin to creatinine ratio to screen for glomerular disease and urine protein to creatinine ratio for tubular diseases, and thresholds were streamlined with the Kidney Disease: Improving Global Outcomes (KDIGO) recommendations. Hepatitis C virus (HCV) treatment recommendations were split into preferred and alternative treatment options. The algorithm for management of recently acquired HCV infection was updated and includes recommendations for early chronic infection management. Treatment of resistant tuberculosis (TB) was streamlined with the World Health Organization (WHO) recommendations, and new tables on immune reconstitution inflammatory syndrome, on when to start ART in the presence of opportunistic infections and on TB drug dosing were included. Conclusions: The EACS Guidelines underwent major revisions of all sections in 2019. They are available in four different formats including a new interactive web‐based version and are translated into Chinese, French, German, Japanese, Portuguese, Russian and Spanish.